Webtoon Festival Daul Madura Sebagai Upaya Pengenalan Budaya Madura Terhadap Remaja Usia 18-22 Tahun - Akbar Firmansyah; Restu Ismoyo Aji; Masnuna Masnuna (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
Madura, an island in East Java, is known for its rich cultural heritage. Despite this, prevailing stereotypes in society often emphasize negative aspects of Madurese culture, which can obscure its valuable and positive traditions. One such cultural gem is Daul music—a vibrant and rhythmic musical expression that deserves greater public appreciation. This study explores the design and development of a digital comic titled “The Sparkle of Madura’s Daul”, which aims to introduce Daul music to a younger audience, particularly teenagers aged 18–22, through the Webtoon platform. Utilizing a qualitative descriptive method, the research gathered data through observation, questionnaires, and interviews to inform the design process. The comic is created not only as an engaging entertainment medium but also as a tool for cultural education and preservation. By integrating narrative and visual storytelling, the comic presents Daul music in a compelling and accessible format, positioning it as a cultural asset comparable to the well-known Karapan Sapi. The final product is intended to reshape perceptions of Madurese identity, promote cultural pride, and encourage the appreciation of traditional music among youth. This initiative highlights the potential of digital media to bridge generational and cultural gaps while revitalizing local heritage through creative means.